(untitled) (Journal of Biomedical Investigation, 2023)
Background: People who grow older may increasingly be at risk for fall and are susceptible to injuries from fall. Fall-related injuries are associated with serious psychological and behavioural consequences including fear of recurrent fall and isolation. It is doubtful if knowledge of fall will be associated with the fall risk profile and safe behavioural practices among elderly. Objective: The objective of this study is to determine if there is any association between knowledge of fall, fall risk profile and safe behaviour among community dwelling adults in Kano metropolis. Methods: A cross-sectional survey of community-dwelling adults (n= 287) was carried out using Fall Knowledge Assessment Questionnaire, Desmond Fall Risk Questionnaire and Fall Behaviour Scale for the Older Persons. A snow balling sampling technique was used to recruit volunteers regardless of their education, gender, socio-economic status and irrespective of walking with aid or not. Results: The results of this study showed that there was a weak significant correlation between the knowledge of fall and fall risk (r = - 0.219, p < 0.05) and no significant correlation was observed between knowledge of fall and behaviour (r = 0.030, p < 0.05) and behaviour and fall risk (r = 0.090, p < 0.05). Conclusion: From the outcome of this study, it was concluded that there was a reciprocal relationship between knowledge of fall and fall risk among this cohort of elderly participants in Kano metropolis.